PENGARUH MEDIA CHEMOPOLY PADA MATERI STUKTUR ATOM TERHADAP HASIL BELAJAR SISWA - Hapsah, Sri; Melati, Husna Amalya; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract This study aims to determine whether or not there are differences in student learning outcomes in class X MIA in SMA Negeri 3 Sungai kakap with atomic structure chemopoly media. The form of research used in this research is quasy experimental design with nonequivalent control group design. The research sample is students of class X MIA 1 namely as an experimental class and Class X MIA 2 as a control class. The results of data analysis of student learning outcomes in the experimental class and the control class using the U-Man Whitney test, showed differences in learning outcomes between students taught using Chemopoly media in the experimental class and student learning outcomes taughtwithout Chemopoly media in the control class on the structure material atom. The results were obtained based on the calculation of the effect size which showed that the magnitude of the influence of Chemopoly media on student learning outcomes was 26.73%. Keywords: Atomic Structure, Chemopoly, Learning Outcomes